Measuring the Redistributive Capacity of Tax Policies - Vellutini, Charles (IMF Working Papers; Working Paper ;, 2021)
This paper presents a novel technique to measure and compare the redistributive capacity of observed tax (or transfer) policies. The technique is based on income distribution simulations and controls for differences in pre-tax income distributions. It assumes that the only information on the pre-tax distribution available in each country-year is the Gini coefficient and the mean (GDP per capita). We illustrate the technique with an application to the personal income tax, using a dataset of 108 countries over the 2007-2018 period.